Intestinal parasitoses and clinical manifestation found in 3 to 12 years old schoolchildren in Argentina - Minvielle, Marta Cecilia; Zubiri, Karina; Ceccarelli, Soledad; De andrea, Maria Jose; Ciarmela, Maria Laura; Pezzani, Betina; Bonzo, Estela (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2018)
We have carried out a study about the frequency of intestinal parasites and the presence of signs and symptoms in 3-12 year-old schoolchildren in the northeast region of the province of Buenos Aires, Argentina, during 2015-2016. For the parasitological study, serial stool analysis and serial anal scraping were done. Through a structured and closed survey applied, the age and sex of each child and the presence of clinical manifestations were recorded. We analized 857 schoolchildren, of which 63.95% were parasitized, with no differences in sex and age; 46.16% monoparasitized, 39% were biparasitized and with three or more parasites 14.84%. The parasitic species detected were: Enterobius vermicularis (50.36%), Giardia intestinalis (28.28%), Blastocystis hominis (61.86%), Ascaris lumbricoides (2.73%) and Trichuiris trichiura (0.91%). Clinical manifestations were registered in 77.59% of schoolchildren, without significant differences between parasitized and non-parasitized. There was a relationship between the number of symptoms/signs and "being parasitized" and between the presence of diarrhea and vomiting with G.intestinalis and B. hominis. According to our results, we suggest: 1-perform parasitological analysis of children with some clinical manifestation and 2- perform parasitological analysis in asymptomatic children with risk factors associated with intestinal parasitosis.